2020
DOI: 10.1002/tea.21646
|View full text |Cite
|
Sign up to set email alerts
|

Invalidated identities: The disconfirming effects of racial microaggressions on Black doctoral students in STEM

Abstract: Black students face repeated racial microaggressions that may challenge their mental health and academic performance in engineering doctoral programs. Researchers attribute this to stereotypes and institutional climates that juxtapose their STEM and racial identities as incongruent. In this article, we analyzed the perceptions of environmental, behavioral, and verbal racial microaggressions of 33 Black doctoral students and postdocs, with a focus on their interactions with non‐Black peers. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 67 publications
(86 reference statements)
0
57
0
Order By: Relevance
“…Therefore, paradoxically, Asian international students can often feel more belongingness within U.S. engineering and computer science doctoral programs than Black domestic students. Black students notice this disparity in social support and some research has suggested that this is exacerbated by language differences, whereby those who are Black domestic students feel excluded by peers due to primary language barriers in increasingly international engineering and computer science doctoral programs within which Asian international students now comprise the majority of doctoral students (Miles, Brockman, and Naphan-Kingery 2020;Okahana and Allum 2015). This is especially problematic due to the fact that STEM disciplines, by nature, are extremely collaborative and require much group work within coursework and laboratory spaces.…”
Section: Sense Of Belonging and Stereotyping In Stemmentioning
confidence: 99%
“…Therefore, paradoxically, Asian international students can often feel more belongingness within U.S. engineering and computer science doctoral programs than Black domestic students. Black students notice this disparity in social support and some research has suggested that this is exacerbated by language differences, whereby those who are Black domestic students feel excluded by peers due to primary language barriers in increasingly international engineering and computer science doctoral programs within which Asian international students now comprise the majority of doctoral students (Miles, Brockman, and Naphan-Kingery 2020;Okahana and Allum 2015). This is especially problematic due to the fact that STEM disciplines, by nature, are extremely collaborative and require much group work within coursework and laboratory spaces.…”
Section: Sense Of Belonging and Stereotyping In Stemmentioning
confidence: 99%
“…In this study, we have understood anyone who has at least one minoritized identity to have the potential for a negatively impacted postdoc experience based on sexism, racism, xenophobia, or any combination of the above, just to name a few (Karalis Noel and Rida, 2020; Karalis Noel, 2019). Collectively, minoritized people are more likely to experience hostile STEM lab environments (Cantwell and Lee, 2010), microaggressions (Miles et al , 2020), be denied access to promotion (McGee, 2021), and experience exclusive environments where their individual identities can impact how they endure STEM environments. The purpose of this work is to illuminate how individuals with at least one minoritized identity are likely to experience oppression within their mentoring experiences with faculty and PIs (Karalis Noel and Rida, 2020; Karalis Noel, 2019).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Minoritized postdocs of color often experience discrimination and isolation. When they interact with others in their fields, they are not always treated as though they are scientists, either comparable to their status as a trained scientist with a doctorate or relative to how other similarly-situated scientists are treated (McGee, 2016; Miles et al , 2020; Nelson and Rogers, 2003). In addition, they do not see many people like themselves represented among their peers and the faculty, making them feel as though they do not belong in these spaces (Malone and Barabino, 2009).…”
Section: Introductionmentioning
confidence: 99%